Peningkatan Kemampuan Membaca Anak TPA Dengan Menggunakan Kartu Kata Bergambar - Sakdiah Sakdiah (Jurnal Dedikasi Pendidikan, 2019)
The ability to read is the basic need for children's progress. Because it needs to be developed early since children are still in kindergarten. The efforts to improve children's reading Syiah Kuala District, Banda Aceh in 2018. This study was aimed to determine whether children's reading ability at the Al-Muhajirin Lamnyong Gumpong Rukoh Syiah Kuala District can be improved by using picture-word cards. The subjects of this study were 22 children, consisting of 12 boys and 10 girls. The method was used with the technique of giving action, namely the use of picture-word cards to read. The actions were conducted in 2 cycles and each cycle consisted of 3 meetings (3 weeks). The parameters observed were reading ability. The data collection instrument used was the observation sheet. The results showed that the ability of children to read at the Al-Muhajirin Lamnyong Gampong Rukoh Syiah Kuala District, Banda Aceh could be improved with picture-word cards..